Analysis of raw potato sorting technology on a potato chip line - Geiger, Audra (Kansas State University, 2013)
Frito-Lay is part of the PepsiCo Family which makes some of the best known and top selling snack foods around. Frito-Lay is the dominant player in the salty snack category in the United States, with a 65 percent share of the market. Frito-Lay brands include Lay's, Ruffles, Tostitos, Sunchips, Fritos, Cheetos, and Doritos. The objective of the thesis is to analyze a potential project: installing a raw potato sorting system on a potato chip line. Part of the analysis will be to conduct a net present value analysis of the costs and benefits associated with the project. Currently the line runs with one full time employee that inspects the raw incoming potatoes for foreign matter and color. Recently, technology options are available that the company could add to the raw potato sorting function that could potentially reduce employee labor costs. This research project provides information regarding the system’s investment cost, maintenance requirements, labor savings, and finished product quality impact. As the business environment changes businesses must keep up with rapidly changing technology to be able to compete. A company that is able to compete will be able to survive in the market and sustain profitability. Capital expenditures need to be evaluated and adopted if they keep a company competitive or make a company more cost efficient. The analysis concluded that the investment of installing a raw potato sorting system would be profitable, earning a positive NPV and internal rate of return greater than Frito-lay’s cost of capital. I would recommend that Frito-Lay move forward with this investment.
Keywords: Technology adoption; Net present value; Internal rate of return; Business (0310); Economics, Agricultural (0503)